Selective laser melting of ceramic-based materials for dental applications - Mahta Mapar (2016)
The employment of the Selective Laser Melting (SLM) technique in the processing of ceramics has attracted attention recently. SLM is a powder-based AM process where powder spreading is one of the fundamental. Therefore, a spray-drying process was chosen to improve powder properties to reach a proper powder for the SLM process. Also a dynamic powder characterisation methodology was used to investigate powder flow characteristic. A series of SLM experiments were conducted using the spray-dried powder in three stages: single-track melting, single-layer melting and fabrication of three- dimensional (3D) blocks (multilayers). The objectives of this set of experiments were to establish the preliminary processing windows of ceramics via SLM. Finally, multilayer or ceramic 3D blocks were experimented via SLM machine. However, the density of the fabricated 3D parts was low and the parts were also fragile and unstable. These results showed that with current state of technology, it is still a challenge to directly fabricate dense ceramic components using SLM. Following the insights obtained from these experiments, the critical challenges of this project were identified and discussed, including ceramic powder layer deposition, laser-powder particles interaction, the dynamic melting and consolidation mechanism, process parameter optimisation and residual stress analysis of the ceramic materials processed with SLM.